Crustal structure of the Kermadec arc from MANGO seismic refraction profiles. Issue 10 (10th October 2016) - Bassett, Dan; Kopp, Heidrun; Sutherland, Rupert; Henrys, Stuart; Watts, Anthony B.; Timm, Christian; Scherwath, Martin; Grevemeyer, Ingo; de Ronde, Cornel E. J.
Abstract: Three active‐source seismic refraction profiles are integrated with morphological and potential field data to place the first regional constraints on the structure of the Kermadec subduction zone. These observations are used to test contrasting tectonic models for an along‐strike transition in margin structure previously known as the 32°S boundary. We use residual bathymetry to constrain the geometry of this boundary and propose the name Central Kermadec Discontinuity (CKD). North of the CKD, the buried Tonga Ridge occupies the fore‐arc with VP 6.5–7.3 km s −1 and residual free‐air gravity anomalies constrain its latitudinal extent (north of 30.5°S), width (110 ± 20 km), and strike (~005° south of 25°S). South of the CKD the fore‐arc is structurally homogeneous downdip with VP 5.7–7.3 km s −1 . In the Havre Trough back‐arc, crustal thickness south of the CKD is 8–9 km, which is up to 4 km thinner than the northern Havre Trough and at least 1 km thinner than the southern Havre Trough. We suggest that the Eocene arc did not extend along the current length of the Tonga‐Kermadec trench. The Eocene arc was originally connected to the Three Kings Ridge, and the CKD was likely formed during separation and easterly translation of an Eocene arc substrate during the early Oligocene. We suggest that the first‐order crustal thickness variations along the Kermadec arc were inherited from before the Neogene and reflect Mesozoic crustal structure, the Cenozoic evolution of the Tonga‐Kermadec‐Hikurangi margin and along‐strike variations in the duration of arc volcanism. Key Points: Three seismic refraction profiles constrain the crustal structure along the Kermadec arc The north Kermadec fore‐arc hosts the Eocene Tonga arc. Back‐arc crustal thickness is 4 km thinner south of the Central Kermadec Discontinuity Along‐strike transitions in crustal structure are inherited and reflect the Cenozoic evolution of the Tonga‐Kermadec margin